Pesniški svetovi "mlade slovenske poezije" 90. let - Plajnšek, Irma (Slavistična revija, 2002)
The contemporary Slovene poetry of fourteen younger poets (born mainly in the 1970's) in the 1990's displays a predictably heterogeneous picture, i.e, in stylistic as well as in thematic and formal aspects of the texts. Poets generally do not reach for experimental and provocative textual processes, butrather in a non-rebellious manner continue the moderation in expression, already typical of the 1980's. In the "young slovene poetry" there is a place for (neo)intimism.
Keywords: intertekstualnost; Intertextuality; poetika; Slovene literature; slovenska književnost; slovenska poezija